Implementasi Pemanfaatan Teknologi Untuk Pembelajaran Inovatif Di Lingkungan Sekolah Dasar - Alindra, Afridha Laily; Afrilia, Afrilia; Hendranti, Alfia Habwah; Deli Setiasari; Handayani, Isna; Syifa, Miana; Pratiwi, Putri Anandika; Layla, Tristia (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
Efforts to improve the quality of learning in primary schools today cannot be separated from the contribution of digital learning media. Technology can make learning more engaging and interactive for students. It supports them in developing creative and innovative skills, which are indispensable to face challenges in the ever-advancing digital age. The purpose of this study is to implement the utilization of technology to improve the quality of learning in primary schools. This research applied a mixed approach with descriptive method, combining quantitative and qualitative data to gain a more comprehensive insight. Data collection was conducted through questionnaires given to students to assess the extent to which technology is used in the learning process, in-depth interviews with teachers to get their viewpoints and experiences, and a literature review that strengthens the theoretical basis. The research findings show that the majority of students are at a moderate to high level of technology use, while teachers and schools are proactively implementing various methods to integrate technology in teaching, although they still face challenges such as lack of facilities and understanding from students. This study provides practical recommendations for schools and policy makers in maximizing technological innovation for the betterment of basic education quality.